Aplikasi Pupuk Organik Pupuk Cair Dari Libah Tahu Berbantu Em-4 Terhadap Pertumbuhan Cabai Merah - Rijal, Muhammad; Syarif, Asrul Bin; Pary, Cornelia; Rosmawati, Rosmawati; Imkari, Sarty; Mutmainnah, Heny (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
This study aims to determine the effect of giving EM-4 to tofu liquid waste on the growth of red chilli (Capsicum annuum L.) and to determine how much influence the application of EM-4 to tofu wastewater on the growth of red chili plants. This type of research is a field experiment research using a quantitative descriptive approach to test the effect of EM-4 on tofu liquid waste on the growth of red chili plants. The research was conducted for two months. The results showed that descriptively there was an effect of giving EM-4 to tofu liquid waste on the growth of red chili plants, namely in the treatment of giving EM-4 to tofu liquid waste by 2% (V1) the average gave the highest yield on all parameters observed, among others, plant height 40.9 cm, stem diameter 0.46 cm, and the number of leaves 68 leaves. The magnitude of the effect of giving EM-4 to tofu liquid waste on the growth of red chili plants based on analysis of variance did not have a significant effect on plant height because the F value of the group (0.61) < Ftable (5.14) and the F value of the treatment (1.23) ) < Ftable (4.76) at a significant level of 5%. The stem diameter also did not have a significant effect because the value of the Fcount of the group (0.50)